Problematics of the Use of Kratom (Mitragyna speciosa) from the Perspective of Criminal Law - Aknes Monika; Ariesta WibisonoAnditya (LEGAL BRIEF, 2026)
The problematic nature of the use and regulation of kratom in Indonesia, from the perspective of criminal law, remains in a state of legal uncertainty due to the absence of explicit regulation within the positive legal system. This study aims to analyze the juridical implications of this normative vacuum and to formulate an ideal and equitable regulatory framework. The research employs a normative legal research method using statutory and conceptual approaches, through an examination of legislation, legal doctrines, and relevant secondary legal materials. The findings indicate that the unclear legal status of kratom gives rise to policy disharmony among state institutions, undermines legal certainty, potentially violates the principle of legality, and creates risks of injustice for society, particularly for farmers and consumers. Furthermore, a purely criminalization-based approach is considered ineffective and may exacerbate the burden on the criminal justice system. This study concludes that the regulation of kratom in Indonesia must be designed in a comprehensive, proportional, and evidence-based manner by positioning criminal law as ultimum remedium, while balancing the interests of public health protection, legal certainty, and socio-economic justice